Peran Filsafat Ilmu dalam Membangun Karakter Peserta Didik Kelas IV Sekolah Dasar pada Era Digital - Muhammad Zulkarnain; Oktaviani; Anna Carolina; Mareta Silaturi; Ana Swita; Darwin Effendi; Hasperi Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has brought about major changes in the world of education, including in the process of character formation of elementary school students. Fourth-grade students are in a developmental phase that begins to show improvements in thinking skills, social interactions, and the formation of values and attitudes. The presence of the internet, digital media, and technological devices provides opportunities for students to acquire broader knowledge, but also presents challenges to character formation. This study aims to examine the role of philosophy of science in building the character of fourth-grade students of SD Negeri 072 Palembang in the digital era. The study used a qualitative approach with a literature study method through the review of various books, articles, and scientific journals. The results of the study indicate that philosophy of science contributes to forming critical thinking patterns, attitudes of responsibility, moral awareness, and ethics in the use of technology in students. The values of philosophy of science can be the basis for strengthening character education so that students not only develop academically, but also have good personalities.